International geo-economic strategy of China: prospects for neoliberal institutionalism and cultural and civilizational tradition (Economic and Political Thought, 2017)
The article aims to analyse China’s international geo-economic strategythat can be described as a dependent variable, i.e. what is explained. To carryout such a research task, two independent variables have been selected:neoliberal institutionalism and China’s cultural and civilizational tradition.This type of research topic solution results from the assumption that China’sinternational objectives and strategy depends on it own tradition (variablesreferring to the features of China’s internal system) and the influence of theinternational system. Taking this into consideration, the author first analysesthe content of international geo-economic strategy in the geo-economic spaceas we;; as measures and methods. He also analyses the content of the assumptionsof one of the most important theories of international relations – theneoliberal institutionalism formulated by an American researcher, RobertKeobene, in the 1990s. Another independent variable analysed concerns China’scultural and civilizational conditions developed in the long history of thecountry and having contemporary anti-tendencies. The next part of the articlerefers to the cultural and civilizational issue and discusses the problem of thespecificity of China’s economic system. It attempts to answer the questionwhether this economy meets demanding criteria or is an example of statecapitalism. In the author’s opinion, it is a key question and the answer to itis important for China’s own assessment of its economic space.